2017
DOI: 10.11604/pamj.2017.28.204.13505
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia in people living with HIV-AIDS in a tertiary hospital in South-East Nigeria

Abstract: IntroductionAcross the globe, human immunodeficiency virus (HIV) infection is a healthcare problem. Dyslipidemia, a cardiovascular risk factor, is known to occur with the progression of HIV infection. The factors which influence dyslipidemia in HIV subjects have not been completely identified. The aim of this study was to evaluate serum lipids and identify the factors which might influence dyslipidemia in treatment-naïve HIV subjects in Owerri, Nigeria.MethodsThis was a cross-sectional study of treatment-naïve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
2
3
5
Order By: Relevance
“…The prevalence of high TG was (24.5%), which lower than previous studies conducted in Uganda (42.1%) [ 47 ], Jordan (41.9%) [ 48 ], (56.1%) [ 49 ], South Africa (59.3%) [ 49 ], Senegal (7.1%) [ 50 ], Malawi (28.7%) [ 51 ], Thailand (49.9%) [ 6 ], and Brazil (65.3%) [ 52 ]. However, this finding is higher than previous studies done in Nigeria (9.9%) [ 53 ]. and Ethiopia (21.0%) [ 54 ].…”
Section: Discussioncontrasting
confidence: 83%
“…The prevalence of high TG was (24.5%), which lower than previous studies conducted in Uganda (42.1%) [ 47 ], Jordan (41.9%) [ 48 ], (56.1%) [ 49 ], South Africa (59.3%) [ 49 ], Senegal (7.1%) [ 50 ], Malawi (28.7%) [ 51 ], Thailand (49.9%) [ 6 ], and Brazil (65.3%) [ 52 ]. However, this finding is higher than previous studies done in Nigeria (9.9%) [ 53 ]. and Ethiopia (21.0%) [ 54 ].…”
Section: Discussioncontrasting
confidence: 83%
“…The prevalence of elevated triglyceride (40.2%) in this study is higher than the previous findings reported in Senegal (7.1%) [37], Nigeria (9.9%) [38], Ethiopia (21.0%) [30], and Malawi (28.7%) [39]. However, it is consistent with the study findings reported in Venezuela (39.7%) [40], Jordan (41.9%) [36], and Uganda (42.1%) [33].…”
Section: Plos Onecontrasting
confidence: 85%
“…Africa (18.5%) [9]. Unlike many previous studies [22,30,38,[42][43][44][45], low HDL-C is the least prevalent component of dyslipidemia in this study. Advanced age, higher BMI, waking less than 150 minutes per week, raised FBG, and medium socio-economic status were significantly associated with a higher risk of dyslipidemia.…”
Section: Plos Onecontrasting
confidence: 66%
“…To further support this, many other studies 9,[21][22][23][24] recorded HDL as the most prevalent lipid type both in local and international studies. The high prevalence of low HDL as shown by Yanai et al 25 in Japan is attributed to less consumption of the poly unsaturated fats.…”
Section: Discussionmentioning
confidence: 81%